If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + -11 = 4x + 6 Reorder the terms: -11 + 3x = 4x + 6 Reorder the terms: -11 + 3x = 6 + 4x Solving -11 + 3x = 6 + 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. -11 + 3x + -4x = 6 + 4x + -4x Combine like terms: 3x + -4x = -1x -11 + -1x = 6 + 4x + -4x Combine like terms: 4x + -4x = 0 -11 + -1x = 6 + 0 -11 + -1x = 6 Add '11' to each side of the equation. -11 + 11 + -1x = 6 + 11 Combine like terms: -11 + 11 = 0 0 + -1x = 6 + 11 -1x = 6 + 11 Combine like terms: 6 + 11 = 17 -1x = 17 Divide each side by '-1'. x = -17 Simplifying x = -17
| (-4)/(q)=(?)/(6q) | | 4p=12z | | log(x+2)+log(x-1)=log(13-2x) | | 9(x-2)=61.2 | | 6(x-2)=61.2 | | x*x*x*x-x*x*x-9x*x-11x-4=0 | | 4x+x+(3+2x)=3x(x-2) | | 2p+wr=r-7g | | https://media.education2020.com/evresources/4072-03-02-06-00_files/i0300000.jpg | | 3s^2-7s-4=0 | | (3-2m)/3=(5-4m)/4 | | 3x+8=6x+28 | | y-3x+4=0 | | 2(y-7)-3y=-(y-3)-12 | | Tan(4*x)=0 | | 3x+(x+5)=70 | | 2x-12+3(x-3)=5+x+2(x-6) | | 3x+(x+4)=70 | | 3y^2+2y-10=0 | | -1/6*9-7 | | 4y + 3 = 2y + 8 | | 6(f+4)=18 | | 4y + 3 = 2y + 9 | | 6x - 5 = 2x + 9 | | 4y + 1 = 2y + 8 | | -8x^4+24x^2-6=0 | | 40 - x = 4 + x | | 2(2l+2)=36 | | 240=20x+30y | | (u-3)*9=18 | | 20y - 16 = 18y - 9 | | -9a+4=24 |